Search for aflatoxin and trichothecene production inhibitors and analysis of their modes of action. Issue 1 (2nd January 2016) - Sakuda, Shohei; Yoshinari, Tomoya; Furukawa, Tomohiro; Jermnak, Usuma; Takagi, Keiko; Iimura, Kurin; Yamamoto, Toshiyoshi; Suzuki, Michio; Nagasawa, Hiromichi
Abstract: Mycotoxin contamination of crops is a serious problem throughout the world because of its impact on human and animal health as well as economy. Inhibitors of mycotoxin production are useful not only for developing effective methods to prevent mycotoxin contamination, but also for investigating the molecular mechanisms of secondary metabolite production by fungi. We have been searching for mycotoxin production inhibitors among natural products and investigating their modes of action. In this article, we review aflatoxin and trichothecene production inhibitors, including our works on blasticidin S, methyl syringate, cyclo(l -Ala-l -Pro), respiration inhibitors, and precocene II. Abstract : :